Analysis of Factors Influencing Consumers in Purchasing Coffee Products of PT Indraco Global Indonesia - Mahardini, Nadia; Heriman, Alfred Setio; Wibowo, Agus Fadil (CV. Civiliza Publishing, 2025)
The purchasing decision process has a very important meaning for the progress of the company. The company can find out how much consumer interest in the products offered and whether the predetermined targets can be achieved or not with the purchasing decision process. This study aims to determine the extent to which product quality, price, and packaging influence the purchase of PT Indraco Global Indonesia's Rasa Sayang coffee. The research approach used was a combination of descriptive and verification, with a sample size of 96 respondents. To ensure the validity and reliability of the research instruments, they were tested. Data analysis methods included multiple regression, multiple correlation, and the coefficient of determination. Based on the study results, product quality does not significantly influence consumer purchasing decisions. Product price significantly influences consumer purchasing decisions. Product packaging does not significantly influence consumer purchasing decisions. On the other hand, product quality, price, and packaging substantially influence purchasing decisions..